ANALISIS KEBIJAKAN PEMERINTAH KOTA CIMAHI DALAM PEMENUHAN HAK ASASI PENYANDANG DISABILITAS DI BIDANG PENDIDIKAN - Fitriyani, Aruni Budi; Riwanto, Agus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This legal research aims to understand the philosophical, sociological, and juridical argumentations in fulfilling educational rights of people with disabilities in Indonesia, to know Cimahi government’s policies in fulfilling educational rights of people with disability in Cimahi, and to know the difficulties facing the government while fulfilling the educational rights of people with disabilities. This research used normative legal research with descriptive research. This research also used primary law material based on regulations and official document, and secondary law material based on law experts’ researches, and tertiary law material based on law dictionary and encyclopedia. The analysis technique used in this research based on qualitative analytical technique which systematically arranged and analyzed using descriptive. The result showed that the philosophical argumentations for the states in fulfilling educational rights of people with disability are based on Pancasila, the sociological argumentations are based on the social fact in the society, and juridical argumentations for the states in fulfilling educational rights of people with disability are based on UUD 1945. There are some policies that Cimahi Government has made in purpose to fulfill the educational rights of people with disability which include inclusive education policies and conducting inclusive education-themed workshops. There are some difficulties that the government has faced while fulfilling education caused by many factors. The first one caused by substantial law, the second caused by structural law, and the third caused by cultural law.